MIGRATION FACTOR OF CONFESSIONAL TOLERANCE IN THE CONTEXT OF MISSIONARY DOMINANTS WITHIN THE BAIKAL REGION OF THE XX-XXI CENTURIES - I. A. Arzumanov (Концепт: философия, религия, культура, 2018)
This article is dedicated to the confessional tolerance and migration factor in the context of the countries in the Baikalsky Region Ministry Studies dominants XX-XXI centuries. Initially, the tolerance as the New Time liberal ideology institute had the meaning in the light of the religiously-confessional liberality. “Dewesternization” reinforcing tendencies are accentuating candidly the opposition in the ideological field. The integration of these factors with the regional emigrational and re-emigrational processes puts the notion of the tolerance to the stage of the national security factor. The culturological approach has been chosen as the basic to analyze the process data. This approach defines the confessional area axiological modes of existence and regional dominant Ministry Studies of the communal traditional institutes and the regional missionary field. The author highlights, that the communal field disintegration processes connected with the Roman Catholic Church missionary as well as non-protestant institutes in the emigrational environment are one of the “westernization” modes of existence of the social and cultural field. Traditional religiously confessional institutes by virtue of the paternalistic tradition of its social political existence have not worked out the missionary methodology which encouraged the effective opposition to the innovations in the confessional field. The juridical policy of Russia and Mongolia, apart from China, is under pressure of the constitutional liberal ideology adopted model. The State practically cannot  retain the status quo of the confessional area traditional institutes “canonical” borders. The organizational and legal means trial implementation to withstand the latent threat of the religious conscience fundamentalization in the empire character objective conditions of the social and political field lead to the basic tolerance principles violation in the religious field.